Importance of Science and Technology Center for learning of physical issues - Santos, E. A.; Souza, D. N. (Scientia Plena, 2012)
This work was carried out with ninth graders, high school and pre-university private and public schools in the city of Itabaiana / SE. Ten visits were conducted with different groups of students, the CCTECA (House of Science and Technology City Aracaju), in order to provide students with a closer contact with experiments and physical phenomena that are present in everyday life. These students were divided into groups for better learning and interaction with the monitors, where they had the opportunity to handle the experiments. During the visit students were accompanied by the coordinators and teachers of the College of Physics and Writing. Students was charged: an essay on the videos viewed in the planetarium, which could explain a dissertation on the importance of the visit to this space for learning, and to do a little explanation of the theory covered in the experiments that most caught his attention. With the information contained in the texts produced by students was evident that there was a great contribution to learning of these students, as well as them having contact with physics experiments, put forward their opinions and relate the physical classroom with the experiments and their daily lives.